PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA MELALUI KEPUASAN KERJA PEGAWAI PADA BADAN KEPEGAWAIAN DAERAH PROVINSI SULAWESI SELATAN - Hidayat, Yusran; Jumady, Edy; Djaharuddin, Dharnawaty (Lembaga Penelitian, Publikasi dan Pengabdian Pada Masyarakat, 2024)
This research aims to determine and analyze the influence of leadership and work environment on employee performance through job satisfaction. This type of research is descriptive research with a quantitative approach. The sample in this study was 56 employees at the Badan Kepegawaian Daerah Provinsi Sulawesi Selatan with the sample collection method using slovin. The data analysis method used is descriptive statistical analysis and path analysis. The research results show that compensation directly has a significant effect on performance. The work environment directly has a significant effect on performance. Job satisfaction directly has a significant effect on performance. Indirectly, compensation has a significant effect on performance through job satisfaction. Indirectly, the work environment has a significant effect on performance through job satisfaction.